PETAT: an ASIC for simple and efficient readout of large PET scanners - Fischer, Peter; Kerschenbauer, Thomas; Ritzert, Michael (Journal of Instrumentation, 2024)
Modern PET scanners based on scintillating crystals use solid state photo detectors for light readout. The small area of these devices is beneficial for spatial resolution, but also leads to a large number of electronic channels to be read out, mostly by application specific integrated circuits (ASICs) containing amplification, noise reduction, hit finding, time stamping and amplitude measurement. Although each ASIC provides up to ≈ 64 channels, a large number of chips is required with the need for auxiliary electronic components like voltage regulators or FPGAs for control and data readout. The FPGAs in turn often require multiple supply voltages and configuration infrastructure, so that PCBs get complicated, cumbersome and power-hungry, in addition to the significant power requirement of the front-end ASICs. We address this issue in the latest generation of our PETA readout ASIC for SiPMs by a simplified control scheme and, in particular, by a hierarchical serial data readout which does not require any additional FPGA. In addition, it provides a time-sorted stream of hit data, allowing early on-detector data reduction and hit pre-processing like the removal of hits with no coincident partner. The simplicity of this readout facilitates a supply scheme where power/ground of multiple ASICs are connected in series instead of the standard parallel connection. This `serial-powering' approach can reduce supply current (while increasing overall supply voltage) so that voltage drop issues in the supply are alleviated.